Znaczenie okresu prenatalnego dla kształtowania się doświadczenia indywidualnego człowieka = The role of prenatal period for individual experience - Klimas-Kuchtowa, Ewa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
It is the common opinion that our individual experience has its beginning at the time when we get intentional admission to our autobiographical memory. On the other hand there are scientific evidences that prenatal period is very important for this process. Because an ear is one of the first senses that develops during human prenatal development it a very important source of our individual experience.
Keywords: słuch w okresie prenatalnym; doświadczenie indywidualne; pamięć autobiograficzna; aural perception during prenatal period; individual experience; autobiographical memory